Transonic static aeroelastic and longitudinal aerodynamic characteristics of a low-aspect-ratio swept wing - Junli Wang (AIP Advances, 2019)
Based on the CFD/CSD coupling method, the transonic static aeroelastic characteristics of the low-aspect-ratio swept wing was studied by numerical simulation. The Navier-Stokes equation was used as the fluid computational control equations. The flow field mesh deformation was performed using the Transfinite Interpolation method (TFI) method, and the data exchange on the CFD/CSD coupling interface was realized by the Constant Volume Transform (CVT) method. Based on the above method, the transonic static aeroelastic coupling calculation program was developed. The results of ONERA M6 wing static aeroelastic calculated by the coupling program were compared with wind tunnel test and reference results, and the effectiveness of the program was verified. Through numerical simulation, the influence of different angles of attack and Mach number on the static aeroelastic deformation and torsion angle of the wing are studied. Finally, by comparing the surface pressure cloud and pressure coefficient of the rigid wing and the elastic wing, the influence of static aeroelastic on the longitudinal aerodynamic characteristics and stability of the wing is mainly analyzed.